Valores intencionais e persuasivos da Língua Japonesa (Estudos Japoneses, 1997)
Starting from the point of view that language is a consequence of sociocultural usages, this paper intends to draw up and discuss some of the conventional values (or crystallizations) developed inside the bounderies of japanese culture which are considered renowned and recognized by their use and that determine and guide the argumentative mechanisms in japanese language.